Pandangan Masyarakat Terhadap Anak Berkebutuhan Khusus Yang Dianiaya Berdasarkan Film Taxi Driver Dengan Kehidupan Nyata - Syakila, Baiq Elga Windis; Yanuar, Galuh Fazry; Noviandi, Rendi; Rodihati, Rodihati; Hamidah, Siti (STAI Denpasar Bali, 2023)
The background of this research is because there are still bad views and behavior by society towards children with special needs (CSN). The writer took one of the Korean dramas which raised the story of the abuse of children with special needs entitled Taxi Driver as a reference for this research. The goal to be achieved from this research is so that people know how to treat children with special needs. This research method uses a quantitative method which is carried out by distributing pamphlets and questionnaires which are distributed through the Google Form media. The results of this research have gotten various respondents regarding their perspectives. From the response we got, not many people still don't really know how to handle children with special needs themselves. However, not a few also argue that the film taxi driver is a treatment that should not be done.